Theoretical Comparative Study on Hydrogen Storage of $BC_3$ and Carbon Nanotubes (Journal of Atomic and Molecular Sciences, 2012)
We have applied the grand canonical Monte Carlo method (GCMC) to investigate the physisorption properties of hydrogen storage in $BC_3$ and carbon nanotubes, respectively. Some important physical amounts under different temperatures and pressures, such as adsorption isotherms and adsorption amounts were studied. The results show that, the physisorption properties of $BC_3$ nanotube are superior to those of carbon nanotube at all conditions. The main reasons causing such different results between them were analyzed from the interaction energies among nanotubes and $H_2$ molecules.
Keywords: $BC_3$ nanotube; hydrogen storage; grand canonical Monte Carlo method (GCMC).